Solid waste management by RDF production from landfilled waste to renewable fuel of Nonthaburi - Udorn Rahotharn; Maneerat Khemkhao; Prangtip Rittichote Kaewpengkrow (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
A worldwide increase in waste production and energy demand as the world's population grows and consumes more resources: therefore, sustainable waste management strategies are important. The goal of this work is to research the guidelines for the appropriate RDF production and landfill waste management of the Nonthaburi province, Thailand. Refuse Derived Fuel (RDF) produced from landfilled Waste (LW) in Nonthaburi was investigated the physicochemical. The following procedure has implemented for the production of LW to RDF of 25 tons/hr of LW; (i) the LW was placed in a pre-shredder, which was followed by a primary crusher; (ii) metals were removed from the waste stream using a magnetic separator; (iii) the LW was transferred using a conveyor belt to a dynamic disc screen, where recyclable waste was separated into smaller sizes less than 80 mm.; (iv) the waste passed through an air separator to reject high-density materials (soil and glass); (v) the undesired material were separated manually, and (vi) the desired material were baled. RDF composition consisted of 78.16-67.93% plastics, 2.29 -4.34% rubber, 1.27% wood, 1.53-2.19 % textile, and other (soil-like material) 12.19-26.72%. The proximate and elemental analysis of RDF was determined according to the ASTM method. The moisture content was reduced, and the heating value increased to 18.08-29.41 MJ/kg. The results suggested high carbon and low nitrogen content suitable for energy conversion. The separation can effectively convert LW to RDF, which can be applied as an alternative fuel. Therefore, RDF can contribute to a more sustainable and circular economy.